PENGEMBANGAN AWAL BAHAN AJAR IPA DI SEKOLAH DASAR - Syofyan, Harlinda; MS, Zulela; Sumantri, M Syarif (Jurnal Pendidikan Dasar, 2019)
The purpose of this study is to develop teaching materials (IPA) thematic-based Integrated grade IV Primary School This research uses research and development methods that recommend the development model of Dick and Carey in developing learning products. From preliminary study through observation, interview and field questionnaire indicated that integrated science learning that took place at SDN Kelapa Dua 06 Pagi, still minimal teaching materials used and teaching materials that have not improved the condition of student inquiry, it is necessary to develop teaching materials (learning ) Integrated Science with integrated thematic based for fourth grade students of elementary school. Validation of teaching materials (learning) is carried out by learning design experts, learning media experts and learning material experts. After the revision was then piloted through a one-to-one test, the results showed that thematic Integrated Science materials based on the 2013 curriculum were in either category. Respondents who participated in this research were fourth grade students of SDN Kelapa Dua 06 Pagi in West Jakarta. The results of the experiments show that the developed materials still need material reduction and specific revisions to produce teaching materials that are in accordance with the needs of the fourth grade students.